NMR and conductivity study of the protonic conductor HPb2Nb3O10 center dot nH(2)O - Tambelli, C. E.; Donoso, J. P.; Magon, C. J.; Angelo, ACD; Florentino, A. O.; Saeki, Margarida Juri [UNESP] (Elsevier B.V., 2000)
Electrical conductivity and H-1 Nuclear Magnetic Resonance (NMR) techniques were used to investigate the ion-exchanged layered lead-niobate perovskite HPb2Nb3O10. nH(2)O, over the temperature range 90-350 K. Compounds were synthesized by the sol-gel method and calcinated at 650 degreesC. Analysis of the NMR data gives activation energies for the proton motion in the range 0.14-0.40 eV, which are dependent on the water content. The frequency and temperature dependencies of the proton spin-lattice relaxation times show that the character of the motion of the: water molecules is essentially two-dimensional, reflecting the layered structure of the material. The H-1 line-narrowing transition and the single spin-lattice relaxation rate maximum, observed in the hydrated compounds, are consistent with a Grotthuss-like mechanism for the proton diffusion. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: NMR; impedance spectroscopy; proton conductor; sol-gel; perovskite